1991
DOI: 10.1080/00071669108417377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high concentrations of dietary vitamin e and ethoxyquin on the performance of laying hens1

Abstract: 1. Three experiments were carried out with light strain laying hens to evaluate the effects of relatively high doses of dietary vitamin E (125 mg/kg food) or ethoxyquin (EQ) (250 mg/kg food) on their laying performance. The control diet contained 5 and 125 mg/kg vitamin E and EQ, respectively. The experimental diets were fed either from one or 32 weeks until 88 or 89 weeks of age. 2. The two antioxidants did not affect the growth of the pullets, age at first egg, final body weight, average egg weight or relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
5
7
1
Order By: Relevance
“…3 g). These data are partly in agreement with Bartov et al (1991), who found that dietary concentration of vitamin E (125 mg/kg food) fed from either one or 32 weeks of age did not affect pullet growth rate, age at first egg or average EW.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 g). These data are partly in agreement with Bartov et al (1991), who found that dietary concentration of vitamin E (125 mg/kg food) fed from either one or 32 weeks of age did not affect pullet growth rate, age at first egg or average EW.…”
Section: Discussionsupporting
confidence: 92%
“…Bartov et al (1991) observed a similar result, in that dietary vitamin E, at 125 mg/kg, could Values in a row not sharing a common superscript are significantly different (P < 0 . 05).…”
Section: Discussionsupporting
confidence: 77%
“…Antioxidants have improved immunity response against stress, including challenges such as coccidiosis (Colnago et al, 1984) and may improve egg production in flocks challenged by some diseases (Bartov et al, 1991). However, supplementation of the diet with ascorbic acid (200 mg/kg) or -tocopherol (75 mg/kg) to adult layers in full production did not change liver malondialdehyde content, glutathione content or liver haemorrhage score in birds predisposed to FLHS (Diaz et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…In chickens, published data dealing with changes in BW with VE supplementation has been also divergent. Decreased (March eta!., 1973;Nockels et al, 1976) or unchanged (McCuaig and Motzok, 1970;Bartov et al, 1991;Sheehy et a!., 1991;Bartov and Frigg, 1992) BW of chickens with high dietary concentrations of VE has been reported in the literature. In other species, high dietary concentrations of VE have been reported to increase BW of calves (Reddy et al, 1987), pigs (Asghar et al, 1991a), and rats (Meydani et al, 1986), and to maintain BW of calves (Arnold etal., 1992), laying hens (Butcher ef al., 1993), and trout (Furones et al, 1992).…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, Bartov et al (1991) found that performance of laying hens did not change when the dietary VE increased from 5 to 125 mg/kg of diet. In contrast, after feeding sunflower oil-based diets containing 200 mg of VE/kg for different periods of time, Lin et al (1989) reported that VE supplementation increased BW and improved FE of chickens from 1 to 7 wk of age, compared with giving the VE only during the last 10 d of the experiment.…”
Section: Discussionmentioning
confidence: 90%